Video migration strategy based on bandwidth demand prediction and cloud resource reservation - ONGXin C; HUANGKai S; USen S; ANGFang-chun Y; ILing-ling Z (Tongxin xuebao)
A video migration strategy which is used in P2P-VoD architecture is presented. First it predicts the bandwidth demands of users in each video channel according to the P2P characteristic. And it gives a basis for migrating videos. Then an algorithm of applying cloud resources which is based on the minimum bandwidth reservation is proposed. It sat-isfies the real-time of VoD service with the costs as low as possible. Finally the video migration strategies are designed to determine the methods of migration videos. The simulation results indicate that the proposed strategy can get good trade-off between costs and user satisfaction.